Efficacy and safety of lenvatinib combined with PD-1/PD-L1 inhibitors plus Gemox chemotherapy in advanced biliary tract cancer - Zhu, Chengpei; Xue, Jingnan; Wang, Yunchao; Wang, Shanshan; Zhang, Nan; Wang, Yanyu; Zhang, Longhao; Yang, Xu; Long, Junyu; Yang, Xiaobo; Sang, Xinting; Zhao, Haitao (Frontiers in Immunology, 2023)
Background: Lenvatinib combined with anti-PD-1 antibodies and systemic chemotherapy has demonstrated a relatively high antitumor activity for intrahepatic cholangiocarcinoma in phase 2 clinical trials. However, its efficacy and safety in advanced biliary tract cancer (BTC) has not been reported in a real-world study. Methods: Patients with advanced BTC who received lenvatinib combined with PD-1/PD-L1 inhibitors plus oxaliplatin and gemcitabine (Gemox) chemotherapy were retrospectively screened. The overall survival, progression-free survival, objective response rate, disease control rate, clinical benefit rate, and safety were evaluated. Results: Fifty-seven patients with advanced BTC were included in the study. The median follow-up time was 15.1 (95% CI: 13.6–19.7) months. The median overall survival and progression-free survival were 13.4 (95% CI: 10.0–NA), and 9.27 (95% CI: 7.1–11.6) months, respectively. The objective response rate, disease control rate and clinical benefit rate were 43.9% (95% CI: 31.8%–56.7%), 91.2% (95% CI: 81.1%–96.2%), and 73.7% (95% CI: 61.0%–83.4%), respectively. Subgroup analysis revealed that the first-line treatment group had a longer median progression-free survival (12.13 vs. 6.77 months, P<0.01) and median overall survival (25.0 vs. 11.6 months, P=0.029) than the non-first-line treatment group. Moreover, three patients underwent conventional surgery after treatment. All patients (100%) experienced adverse events, and 45.6% (26/57) experienced grade 3 or 4 adverse events. The most commonly observed grade 3 or 4 adverse events was myelosuppression (7/57, 12.3%). No grade 5 adverse events were reported. Conclusion: Lenvatinib combined with PD-1/PD-L1 inhibitors and Gemox chemotherapy represents an effective and tolerable treatment option in patients with advanced BTC.